2006
DOI: 10.1523/jneurosci.3225-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Completion Is Automatic and Dissociable from Shape Discrimination

Abstract: Normal visual perception readily overcomes suboptimal or degraded viewing conditions through perceptual filling-in processes, enhancing object recognition and discrimination abilities. This study used visual evoked potential (VEP) recordings in conjunction with electrical neuroimaging analyses to determine the spatiotemporal brain dynamics of boundary completion and shape discrimination processes in healthy humans performing the so-called "thin/fat" discrimination task (Ringach and Shapley, 1996) with stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
127
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 55 publications
(75 reference statements)
22
127
1
1
Order By: Relevance
“…The IC effect is likewise unaffected by participants' accuracy in discriminating the curvature of the induced contours and also occurs prior to modulations of the concavity/convexity of the perceived contour [37], prompting at least two conceivable interpretations. First, IC sensitivity may dissociate from and precede shape discrimination.…”
Section: The Salient Region Hypothesismentioning
confidence: 94%
See 1 more Smart Citation
“…The IC effect is likewise unaffected by participants' accuracy in discriminating the curvature of the induced contours and also occurs prior to modulations of the concavity/convexity of the perceived contour [37], prompting at least two conceivable interpretations. First, IC sensitivity may dissociate from and precede shape discrimination.…”
Section: The Salient Region Hypothesismentioning
confidence: 94%
“…Murray et al [25] found that sensitivity to Kanizsa-type ICs onsets at ~90ms post-stimulus onset (see also [33] for initial evidence for such timing and [34] for an alternative paradigm yielding similar results), lagged ERP onset by ~40ms, and is localized first to the LOC (Figure 2). This "IC effect" has been shown to be an amplitude rather than a topographic modulation of the ERP that is superimposed upon the so-called N170 component [28]( [8,[35][36][37][38]), which is a peak of the visual evoked potential at ~150-200ms with a negative distribution of the parieto-occipital scalp with predominant sources within ventral and lateral occipital cortices. In addition, the IC effect is insensitive to variations in the contrast polarity (i.e.…”
Section: Electroencephalography and Magnetoencephalographymentioning
confidence: 99%
“…This clustering procedure identifies the topographies (ie maps) dominating the group-averaged AEPs across populations/ conditions. The pattern observed at the group-average level was then statistically assessed at the individual participant level using a fitting procedure based on spatial correlation (Brandeis et al, 1995; see also Murray et al, 2006, for a recent publication of formulae), yielding a measure of map presence. These values are then submitted to ANOVA, revealing whether and when different maps explain CGI and PANSS scales: S, severity; I, improvement; P, positive; N, negative; G, general psychopathology; T, total score.…”
Section: Eeg Recordings and Analysesmentioning
confidence: 99%
“…the topography of the electric field at the scalp) as well as latency shifts in brain processes across experimental conditions. Because the electrophysiological methods have been extensively detailed previously Murray et al, 2004;De Santis et al, 2007; for a recent publication of formulas, see Murray et al, 2006), we provide only the essential details here.…”
Section: Eeg Analyses and Source Estimationmentioning
confidence: 99%
“…In other words, the methods described above generate a hypothesis concerning the sequence of maps observed in the AEPs and any differences between stimulus positions and/or sessions. To statistically assess this hypothesis, each time point of each AEP from each subject was labeled according to the map with which it best correlated spatially (Brandeis et al, 1995;Murray et al, 2006). We, hereafter, refer to this procedure as "fitting."…”
Section: Eeg Analyses and Source Estimationmentioning
confidence: 99%